MYOPIA PREDICTORS AS A STARTING POINT FOR ACTIVE PREVENTION OF MYOPIA DEVELOPMENT - E. P. Tarutta; O. V. Proskurina; N. A. Tarasova; R. A. Ibatulin; A. S. Kovychev (Российский офтальмологический журнал)
The review gives a detailed account of research data on myopia predictors. The most reliable predictors include cycloplegic sphere equivalent of axial refraction less than +0.75 D in children under 6 years, the axial length of more than 23.5 mm with the refractive error ≤ +1.0 D, myopic parents, axial length / corneal radius ratio (AL/CR) of less than 3, AC/A ratio over 4 Δ/D, pseudomyopia, heterophoria of more than 4 Δ, peripheral refraction of the nasal half of the eye at 20-30° higher than the temporal refraction in both eyes more than 0.5 D, reduced outdoor activity and high visual activity. Measures of prevention of myopia development are presented: adhering to the regiment of visual activity load, ergonomic stereotypes of near visual work, creation of binocular central and peripheral myopic defocus - positive spectacles or spectacles with Perifocal-P lenses with a central refraction of +0.25 D for permanent wear, home accommodative training exercises, physical exercises and sports, outdoor activity at least 90 minutes a day during daylight hours. For citation: Tarutta E.P., Proskurina O.V., Tarasova N.A., Ibatulin R.A., Kovychev A.S. Myopia predictors as a starting point for active prevention of myopia development. Russian ophthalmological journal. 2018; 11 (3): 107-12 (In Russian). doi: 10.21516/2072-0076-2018-11-3-107-112